A Review of Tissue Expansion-Assisted Techniques of Cleft Palate Repair. Issue 3 (May 2016) - Shash, Hani; Al-halabi, Becher; Jozaghi, Yelda; Aldekhayel, Salah; Gilardino, Mirko S.
Abstract : Background: The purpose of this report was to examine current knowledge of use of tissue expansion techniques to assist cleft palate repair and to review and contrast various techniques reported. Methods: Two separate literature searches were conducted in the Cochrane Library, CINAHL, Medline and Embase databases, from database inception until December 2014 for use of mucoperiosteal expansion (MPE) and distraction osteogenesis (DO) in cleft palate repair. Results: Six articles, reporting a total of 51 patients of palatal MPE, were identified for discussion and analysis. Three different MPE techniques in primary cleft palate repair were described: intraoperative rapid expansion, tumescent injections, and a 2-stage repair with an osmotic expander. Average fistula rate was 26.19%. The search for use of DO on palatal clefts revealed 6 animal models, a finite element analysis study, and 1 case report. Moreover, 2 patients were reported of the use of DO to assist in secondary palatal fistula closure. No fistula rate could be calculated due to the heterogeneity of the data. Conclusions: The experience with MPE in assisting cleft palate repair remains limited. Among expansion techniques, the use of osmotic expanders was associated with the highest rates of postoperative fistulae. The literature provides little evidence supporting the efficacy of MPE expansion in cleft palate repair. The majority of studies utilizing DO to assist primary cleft palate repair are in animal models with the exception of isolated case reports in human subjects. Although limited, the results demonstrate promise and the need for further research in this domain.